2007
DOI: 10.2111/1551-5028(2007)60[253:iagsoi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Is Altering Grazing Selectivity of Invasive Forage Species With Patch Burning More Effective Than Herbicide Treatments?

Abstract: Is altering grazing selectivity of invasive forage species with patch burning more effective than herbicide treatments?. Rangeland Ecology & Management, 60(3), 253-260.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 25 publications
2
64
1
Order By: Relevance
“…The preference or focusing of grazing in a particular area (large or small) will influence vegetation community and characteristics. The continued attraction of both bison and cattle to recently burned areas alters vegetation structure which affects biodiversity , fire behavior (Leonard et al 2010), invasive species populations (Cummings et al 2007), invertebrate populations and communities (Engle et al 2008), and nutrient cycling and distribution . The preference of riparian and woody vegetation areas by cattle will also likely result in vegetation and system changes.…”
Section: Discussionmentioning
confidence: 99%
“…The preference or focusing of grazing in a particular area (large or small) will influence vegetation community and characteristics. The continued attraction of both bison and cattle to recently burned areas alters vegetation structure which affects biodiversity , fire behavior (Leonard et al 2010), invasive species populations (Cummings et al 2007), invertebrate populations and communities (Engle et al 2008), and nutrient cycling and distribution . The preference of riparian and woody vegetation areas by cattle will also likely result in vegetation and system changes.…”
Section: Discussionmentioning
confidence: 99%
“…PTC is a North American native (Diggs et al 1999), and SL, native to Asia, is naturalized throughout the southern USA (Cummings et al 2007). PTC and SL seeds were germinated in growth chambers in March 2012, and, after three weeks, plants were transplanted in a greenhouse into 1.9 L containers filled with topsoil (A and B horizons) Mehlich 1984).…”
Section: Plant Speciesmentioning
confidence: 99%
“…Prescribed burning within IAPdominated ecosystems will break down mature tissue and litter, which in turn will increase light and nutrient availability and stimulate germination from the seed bank and vegetative growth. Because of this flush of resources, plant species that colonise after fire will be more palatable and nutrient rich, and these patches will then attract grazing stock and reduce selective pressure (Cummings et al 2007). In some cases, prescribed burning may reduce dominant IAPs and promote other desirable species without livestock grazing being necessary, although evidence has shown that prescribed burning is more effective when incorporated into an integrated vegetation management program (DiTomaso et al 2006).…”
Section: Control Strategiesmentioning
confidence: 99%
“…Patch burning was found to reduce invasion in tallgrass prairies by maintaining the invasive species in a young and palatable stage of growth (Cummings et al 2007). The size of the patch that is burnt matters, however, with small burnt patches more likely than large ones to result in increased grazing pressure on all species present not just the most palatable.…”
Section: Control Strategiesmentioning
confidence: 99%